PENGARUH VARIASI WAKTU EKSTRAKSI TERHADAP KADAR SAPONIN TOTAL EKSTRAK AIR AKAR TEBU HITAM (Saccharum officinarum L.) SECARA SPEKTROFOTOMETRI UV-VIS - Sarwendah, Adzkia Salsa; Lindawati, Novena (Kartika : Jurnal Ilmiah Farmasi, 2024)
Black Sugar Cane (Saccharum officinarum L.) is an annual plant that is often used for medicine, food and, drink. Black Sugar Cane Root decoction has various pharmacological effects as antibacterial, immunomodulatory and antianemic due to the presence of saponins. This study aims to determine total saponin levels with variations in boiling time for Black Sugar Cane Roots using the UV-Vis Spectrophotometry method. The method for identifying saponin compounds uses the foam method and Liebermann-Burchard reagent. Determination of levels was carried out using the UV-Vis Spectrophotometry method at a wavelength of 543 nm and an operating time of 15 minutes. The comparison standard used is Diosgenin. The results showed that the decoction of Black Sugar Cane Roots positively contained steroid saponins. The results of determining total saponin levels with varying boiling times of 10 minutes, 20 minutes, and 30 minutes were respectively 1.123 mg DE/g with a KV of 0.679%, 2.086 mg DE/g with a KV of 0,276%, and 2.933 mg DE/g with KV 0.196%, the boiling time is 30 minutes, Black Sugar Cane Roots have the highest saponin content. Homogeneity of Variences Test, a significance value of 0.641 > 0.05 was obtained. The Anova test obtained a significance value of 0.000 < 0.05, that there is a significant difference between the saponin content and the boiling time for Black Sugar Cane Roots.